Modeling of Inscribed Dual Band Circular Fractal Antenna for Wi‐Fi Application Using Descartes Circle Theorem - SatheeshKumar Palanisamy; Anitha R. Vaddinuri; Arfat Ahmad Khan; Muhammad Faheem (Engineering Reports)
ABSTRACT This study focuses on the modeling of a dual‐band circular fractal antenna designed for Wi‐Fi applications by utilizing the Descartes Circle Theorem. The antenna's geometry is characterized by self‐similar fractal patterns, enabling enhanced performance in dual frequency bands relevant to Wi‐Fi communication. Current research is trending towards the development of antennas capable of operating across various Wi‐Fi bands, and the emerging 6 GHz band. In this article, there is also a focus on achieving ultra‐wideband functionality to cater to the requirements of future wireless technologies. Incorporation with Circuits and Systems: Ongoing efforts are directed at seamlessly integrating these antennas with RF circuits and communication systems to enhance their practical utility and applicability. The exploration of unconventional fractal shapes and the utilization of advanced optimization algorithms present promising avenues for enhancing antenna performance and achieving miniaturization. This research contributes to the advancement of compact and efficient antenna designs for wireless communication systems. Detailed considerations are given to the 2.4 and 5.55 GHz bands to ensure compatibility with standard Wi‐Fi protocols. The designed circular fractal antenna is compared with the conventional circular patch antenna and the results were analyzed. At the resonating frequency of 2.4 and 5.55 GHz, circular patch antenna has a reflection coefficient (S11) of −18.1 and −13.51, respectively with a peak gain of 3.6 dBi, whereas, the designed circular fractal antenna shows an improved reflection coefficient, S11 of −22.0 and −15.5 dB at the same resonating frequency with a peak gain of 11.7920 dBi. The radiation pattern shows that the antenna radiated in unidirectional pattern with the front‐to‐back ratio of 101.4 which is higher than circular patch antenna. The miniaturized antenna is fabricated through photo etching process, tested, and validated.